Analysis Of Factors Affecting Learning Difficulties Of Class XII Students Of SMAN 2 Bolo - Awaluddin, Rizka; Mahrun, Mahrun; Ardiansyah, Ardiansyah; Rais, Amin (Justek : Jurnal Sains dan Teknologi, 2023)
Abstract: This research aims to analyze the factors that influence students' difficulties in learning. The type of research used is descriptive with a quantitative approach. The population in this research is all students of class XII MIPA SMAN 2 Bolo which consists of four classes with a total of 121 students. Meanwhile, in determining the sample, purposive sampling was used, namely those used as samples in this study were class XII MIPA students at SMAN 2 Bolo who had scores below the Minimum Completeness Criteria (KKM). The instrument used to identify factors that hinder students' learning difficulties is a questionnaire consisting of 35 statement items. Data analysis uses the index % formula then the data is categorized to interpret the factors of student learning difficulties. The results of the research show that the factors that influence students' learning difficulties, the indicators of student readiness and attention are 64% including the inhibiting category, interest and motivation are 71% in the inhibiting category, the learning process indicators are 78% in the inhibiting category, the learning facilities indicators are 72% the inhibiting category and the parental role indicator is 68% of the inhibiting category.Abstrak: Penelitian ini bertujuan untuk menganalisis faktor-faktor yang mempengaruhi kesulitan siswa dalam belajar. Jenis penelitian yang digunakan adalah deskriptif dengan pendekatan kuantitatif. Adapun yang menjadi populasi dalam penelitian ini adalah seluruh siswa kelas XII MIPA SMAN 2 Bolo yang terdiri atas empat kelas dengan jumlah siswa 121 orang siswa. Sedangkan dalam penentuan sampel menggunakan purposive sampling yakni dimana yang dijadikan sampel dalam penelitian ini yaitu siswa kelas XII MIPA SMAN 2 Bolo yang memiliki nilai dibawah Kriteria Ketuntasan Minimal (KKM). Instrumen yang digunakan untuk mengidentifikasi faktor-faktor yang menghambat kesulitan belajar siswa yaitu kuesioner berjumlah 35 item pernyataan. Analisis data menggunakan rumus index % kemudian data dikategorikan untuk menginterpretasikan faktor-faktor kesulitan belajar siswa. Hasil penelitian menunjukkan bahwa faktor-faktor yang mempengaruhi kesulitan belajar siswa, pada indikator kersiapan dan perhatian siswa sebesar 64% termasuk kategori menghambat, minat dan motivasi sebesar 71 % kategori menghambat, indikator proses pembelajaran sebesar 78 % kategori menghambat, indikator fasilitas pembelajaran sebesar 72% kategori menghambat dan indikator peran orang tua sebesar 68 % kategori menghambat.